Research advances on postbiotics in promoting skin wound healing: mechanisms, formulations, and clinical translation - Yu Xing; Jinyu Song; Bingbing Shang; Guangdi Yang; Ye Zhao; Ming Li; Binbin Hou (Frontiers in Immunology, 2026)
Wound healing is a complex process involving different cell types, molecules and stages in the dermis, epidermis and associated microbiome. Chronic wounds caused by pressure, diabetes, or immunodeficiency often have huge economic and therapeutic costs. Postbiotics, in particular inactivated bacteria, cell components and metabolites, are emerging as novel treatments targeting the skin microbiome and provide precise treatment options for wound healing, inflammation, angiogenesis and re-epithelialization. We review the positive regulatory role of different microbial communities in skin healing; evaluate evidence and mechanisms of various postbiotics, in vitro and in vivo models as well as preliminary clinical studies; and summarize progress in the translation of postbiotics for skin wound repair.